Phytochemical of Mikania micrantha - Mohd Sabri, Noor Fatien Syahieda (2018)
Mikania micrantha known as “selaput tunggul”, is a medicinal plants that used as traditional medicine, belongs to family Asteraceacea. It is used to treat several diseases like external wound, cancer, skin itches, fever, respiratory deseases etc. It also shows antioxidant,antimicrobial and anti- stress activities. The present study was carried out to identify extractive values on different types of solvent and part of plant and to analyse the phytochemical and total phenolic content. The hot water extract on leaf was found has the highest yield with (27.64%) followed by cold water (24.11%), methanol (18.79), ethanol (17.08) and petroleum ether (4.11%) respectively. In stem the most extractive value was found in hot water (19.71%) followed by methanol (16.71), ethanol (14.81), cold water (12.71) and petroleum ether (0.87%) respectively. For total phenolic content, the highest concentration of phenols was measured in hot water extract, (325.28±2.28) for stem and (335.5±2.37) for leaves, followed by methanol extract for leaves (241.91± 1.72) and stem (196.63± 1.41) extract. Petroleum ether extracts contained the lowest TPC (26.87± 0.24) and (9.37± 0.10) for leaves and stem respectively Phytochemical investigation of M.micrantha revealed the presence of various important secondary metabolites such as alkenes hydrocarbon, fatty acid, phenol and alcohol.